Improving The Understanding Of Research Methodology And Self-Regulated Learning Through Blog Project - Retnawati, Heri (LPMPP Universitas Negeri Yogyakarta, 2017)
Abstract: This classroom action research seeks to improve self-regulated learning (SRL) and understanding of research methodology at the graduate school. Nineteen graduate school students were involved. Using project-based learning (PjBL), students were assigned to create online blogs as the main project. The blog was intended for representing their understanding of research methodology by writing review of research articles and submitting a research proposal. The classroom action research was based on a model by Kemmis McTaggart and was conducted in two cycles. The data were analyzed using mixed methods in which the main data were analyzed qualitatively and further analysed quantitatively. The results of the study showed that after completing the course, students not only gained knowledge about research methods, but were also able to write a research proposal. In addition, the project-based learning could facilitate students to practice their communication skills while writing on their blog and to improve self-regulated learning. Keywords: Action research, project-based learning, blog, self-regulated learning PENINGKATAN PENGUASAAN METODOLOGI PENELITIAN DAN SELF REGULATED LEARNING MELALUI PROJEK BLOG Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan kemandirian belajar dan pemahaman metodologi penelitian di sekolah Pascasarjana. Partisipan yang terlibat pada studi ini adalah 19 mahasiswa master di sekolah pascasarjana. Dengan menerapkan pembelajaran berbasis projek (PjBL), mahasiswa diberi tugas membuat blog sebagai projek utama. Projek yang dibuat mahasiswa berupa blog untuk merepresantasikan pemahaman metodologi penelitian mahasiswa melalui tulisan dan usulan penelitian tesis. Penelitian tindakan ini dilaksanakan dalam dua siklus dengan model Kemmis Taggart. Analisis data dilakukan dengan mixed methods secara kualitatif dengan dilengkapi analisis kuantitatif sebagai pendukung. Hasil studi menunjukkan bahwa setelah menyelesaikan perkuliahan, selain memperoleh ilmu tentang metode penelitian, dengan pembelajaran berbasis proyek dihasilkan pula calon proposal penelitian. Keunggulan lain adalah dapat melatih kemampuan komunikasi mahasiswa melalui blog dan dapat meningkatkan self regulated learning. Keywords: action research, project-based learning, blog, self regulated learning